PERANCANGAN MESIN PENGUPAS KULIT KENTANG KAPASITAS 5 KG - nalahuddin, Muchlisi; Ananda Putra, Arief Try; Leni, Desmarita (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2024)
Furthermore, in the development of this potato peeling machine, human resources play a crucial role. The This study presents the development of a potato peeling machine focusing on structural reliability and efficiency. Human resources play a crucial role in this development. The machine uses L-shaped iron profiles and stainless steel plates, aligning with sustainable and recyclable materials for environmental compatibility.An analysis of the machine's shaft, made of AISI 1045 steel with a 20 mm diameter, shows high structural reliability for efficient potato peeling. The machine is designed with a 5 kg capacity, integrating 30x30x3 mm L-shaped iron profiles and stainless steel plates. Powered by a 1/4 HP electric motor, the machine measures 500 x 500 x 892 mm, including a peeling cylinder of 35 cm diameter and 34 cm height, with shaft support from P204 bearings.Frame structure analysis under a total load of 50 kg reveals maximum and minimum stress values of 69.44 MPa and 2.055e-11 MPa, both below the ASTM A36 steel yield strength limit of 250 MPa. Maximum and minimum displacements are 0.39076 mm and 1.00e-30 mm. Safety factor analysis yields maximum and minimum values of 1.217e+13 and 3.575, exceeding the recommended range for static loads. In conclusion, the heavy-duty machine frame is safe and suitable for the proposed design, ensuring safety and optimal performance. The machine combines structural reliability with operational efficiency, ideal for peeling potatoes. The use of high-quality materials and detailed structural analysis ensures durability and performance, setting a new benchmark for agricultural equipment.